Das consultas terapÃªuticas Ã consulta conjunta: contribuiÃ§Ãµes de Winnicott Ã prÃ¡tica do apoio matricial /From therapeutic consultations to joint consultation: Winnicott's contributions to matrix support practice - Vieira, Gustavo; Castanho, Pablo (Ciência & saude coletiva, 2022)
The scope of this article is to revisit the Therapeutic Consultations of psychoanalyst Donald Winnicott, seeking to identify technical and ethical contributions which can strengthen the "matrix support" and joint consultations in the Unified Health System (SUS). A rereading of Winnicott's texts and those of commentators is conducted, presenting a debate between the author's ideas and the work in mental health in primary care. Based on detailed case analysis, the article addresses some implications for the practice of matrix support, both in the intervention by the team, and in listening to the patient and family members. In addition, based on a contextualized study of Winnicott's consultation reports, the work presents contributions for joint consultations in the SUS, both in its care and in its formative axis. The following stand out in terms of technical and ethical results: (a) the priority of listening directly to the person who gave rise to the complaint; (b) the importance of sustaining "space and time" to allow a meaningful experience for the patient; (c) the use of interview instruments in the light of "shared playing"; (d) the patient as an active subject in the construction of his therapeutic project; (e) the importance of the local team in supporting and "translating' the patient's experience.